SINERGITAS PEMERINTAH DAERAH KABUPATEN INDRAGIRI HILIR DAN PEMERINTAH DESA TANJUNG PASIR DALAM PENGEMBANGAN FESTIVAL MENONGKAH TAHUN 2016-2018 - Ayu Feby Fitriani; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Menongkah Festival is a cultural tourism concept that is a characteristic of the Duanu tribe in Indragiri Hilir Regency. Menongkah Festival is a cultural tourism that has local wisdom. The Menongkah Festival is jointly managed by the Regional Government of Indragiri Hilir Regency and the Tanjung Pasir Village Government. Funds budgeted for the Menongkah Festival are still very minimal, due to the development of the Menongkah Festival and the procurement of facilities and infrastructure are not going well. Therefore, a good synergy is needed so that the development of the Menongkah Festival can be developed well.This study aims to determine the synergy of the Regional Government of Indragiri Hilir Regency and the Tanjung Pasir Village Government in the development of the 2016-2018 Menongkah Festival. This research used descriptive qualitative method with data collection techniques through interviews and documentations.Based on the results of the study showed that the Synergy of the Regional Government of Indragiri Hilir Regency and the Tanjung Pasir Village Government in the development of the Menongkah Festival are as follows: 1) The Regional Government of Indragiri Hilir Regency and the Tanjung Pasir Village Government are still lacking in conducting synergy. Thus, the development of the Menongkah Festival is not going well. 2) Lack of synergy in the implementation of the Festival of Menongkah which causes a decrease in the number of tourist visits, inadequate transportation, lack of service facilities such as facilities and infrastructure that can support the development of the Festival of Menongkah, and a lack of tourism promotion carried out that there are many people who are still not familiar with the Festival of Menongkah . The inhibiting factors of the synergy between the Regional Government of Indragiri Hilir Regency and the Tanjung Pasir Village Government are: 1) Lack of communication by the two related agencies in the development of the Menongkah Festival. 2) Lack of coordination that there is no harmonization of policies taken between agencies in the development of the Menongkah Festival. 3) The location is quite far and accessibility requires a lot of time and money. 4) Lack of budget in the implementation of the Menongkah Festival. Keywords: Local Government, Village Government, Synergy, Menongkah Festival